Desert springs: deep phylogeographic structure in an ancient endemic crustacean (Phreatomerus latipes). - Michelle T Guzik (Public Library of Science (PLoS), 2012)
Desert mound springs of the Great Artesian Basin in central Australia maintain an endemic fauna that have historically been considered ubiquitous throughout all of the springs. Recent studies, however, have shown that several endemic invertebrate species are genetically highly structured and contain previously unrecognised species, suggesting that individuals may be geographically 'stranded in desert islands'. Here we further tested the generality of this hypothesis by conducting genetic analyses of the obligate aquatic phreatoicid isopod Phreatomerus latipes. Phylogenetic and phylogeographic relationships amongst P. latipes individuals were examined using a multilocus approach comprising allozymes and mtDNA sequence data. From the Lake Eyre region in South Australia we collected data for 476 individuals from 69 springs for the mtDNA gene COI; in addition, allozyme electrophoresis was conducted on 331 individuals from 19 sites for 25 putative loci. Phylogenetic and population genetic analyses showed three major clades in both allozyme and mtDNA data, with a further nine mtDNA sub-clades, largely supported by the allozymes. Generally, each of these sub-clades was concordant with a traditional geographic grouping known as spring complexes. We observed a coalescent time between ∼2-15 million years ago for haplotypes within each of the nine mtDNA sub-clades, whilst an older total time to coalescence (>15 mya) was observed for the three major clades. Overall we observed that multiple layers of phylogeographic history are exemplified by Phreatomerus, suggesting that major climate events and their impact on the landscape have shaped the observed high levels of diversity and endemism. Our results show that this genus reflects a diverse fauna that existed during the early Miocene and appears to have been regionally restricted. Subsequent aridification events have led to substantial contraction of the original habitat, possibly over repeated Pleistocene ice age cycles, with P. latipes populations becoming restricted in the distribution to desert springs.